The prognostic utility of no evidence of disease activity (neda). Issue 5 (8th May 2017) - Lu, Grace; Beadnall, Heidi; Wang, Chenyu; Hardy, Todd; Barton, Joshua; Barnett, Michael
Abstract : Objectives: To investigate NEDA-3 and NEDA-4 status over one year in a group of heterogeneously treated patients with relapsing-remitting multiple sclerosis (MS). To investigate the prognostic utility of NEDA-3 status at 3 months for NEDA-3 at 12 months. Methods: Sixty-nine patients with relapsing-remitting MS were recruited from the MS Clinic, Brain and Mind Centre, Sydney. Patients underwent clinical assessments, including an Expanded Disability Scale Status (EDSS), and MRI at baseline, 3 and 12 months. NEDA-3 was defined as; i) the absence of clinical relapses, ii) no 3 month confirmed disability progression, and iii) no new/enlarging T2 lesions or gadolinium-enhancing lesions. NEDA-4, determined at 12 months was defined as NEDA-3 plus the inclusion of a fourth measure, iv) no annualised brain atrophy of >0.4%. Results: Of the participants, 84.1% were female, mean (SD) age was 37.1 (9.1) years, mean EDSS score 1.9 (1.4), average disease duration 7.6 (7.1) years and all patients were on disease-modifying therapy (DMT). At 3 months, 47.83% of the cohort had NEDA-3. Between 3 and 12 months, 36.23% had NEDA-3. Between 0 and 12 months, 23.19% had NEDA-3% and 13.04% achieved NEDA-4 status. The positive predictive value of NEDA-3 status at 3 months for 12 months was 39% (95%CI 23 to 58). Negative predictive value was 67% (95%CI 49 to 81), sensitivity 52% (95%CI 31 to 72) and specificity 55% (95%CI 39 to 70). Conclusions: NEDA-3 was achieved more frequently than NEDA-4, suggesting significant disease progression in a proportion of patients despite the absence of traditional clinical and MRI metrics of disease activity. In this heterogeneous cohort, NEDA-3 at 3 months was not useful in predicting those who would maintain NEDA-3 at 12 months, emphasising the need for regular clinical and radiological assessment in MS. In this real-world patient cohort, disease progression occurred despite DMT in most patients, emphasising the need for improved treatment escalation paradigms in MS.